Audit services and financial reporting quality: The role of accounting expertise auditors - Shujah-Ur- Rahman; SongSheng Chen; Mamdouh Abdulaziz Saleh Al-Faryan; Ilyas Ahmad; Rana Yassir Hussain; Shah Saud (Cogent Business & Management)
The effectiveness of the company’s financial reporting system depends on the audit’s quality. In this context, the current study examines the role of accounting and financial expertise (AFE) auditors for financial reporting quality (FRQ). Since numerous components work together to determine financial reporting quality, measuring financial reporting quality is intrinsically complex. In this regard, the reporting quality (IFRQ) is measured by using a comprehensive Index of Financial Reporting Quality. Our study’s core and robust findings showed that the sample firms’ financial reporting quality was greatly improved by having AFE directors on the audit committee. Additionally, the current study has revealed that AFE auditors greatly cut real earnings management and improved accruals quality (alternative proxies of FRQ). By using the Generalized Method of Moments (GMM) econometric technique, which controls endogeneity, simultaneity, and unobserved heterogeneity, our research has shown that the audit committee’s accounting and financial competence directors play a unique role. This study may be useful for organizational leaders and policymakers from a practical standpoint.